Interventions for alcohol and drug problems in outpatient settings: A systematic review. (11th March 2013) - Watson, Judith M.; Fayter, Debra; Mdege, Noreen; Stirk, Lisa; Sowden, Amanda J.; Godfrey, Christine
Abstract Issues Research evidence indicates a high prevalence of substance abuse among patients presenting in general hospital settings. Such misuse of alcohol and illicit drugs has a major impact on population health and on costs to health services and to society at large. This review aimed to identify the interventions for alcohol or illicit drug misuse problems that have been evaluated for hospital outpatient populations. Approach Thirteen electronic databases including MEDLINE, EMBASE and PsycInfo were searched for published and unpublished studies in any language up to August 2011. Reference lists of included studies and reviews were also hand‐searched. We included randomised and controlled clinical trials of any intervention for adult participants identified as having alcohol and/or drug problems presenting to hospital outpatient settings other than addiction or psychiatric units. Participants could be attending hospital for any reason other than treatment for substance abuse. A narrative synthesis was conducted. Key Findings There is some evidence to suggest that interventions based on motivational techniques might be effective in treatment of alcohol misuse in oral–maxillofacial clinics but not in general outpatient departments. The evidence is insufficient to allow any conclusions to be derived on the effectiveness of interventions in the treatment of drug misuse and combined alcohol–drug misuse in outpatient settings. Conclusions Further research is needed to investigate interventions for alcohol and drug misuse in outpatient settings. Additionally, problems remain in terms of study quality. Procedures to ensure the rigour of a study were often poorly reported. [Watson JM, Fayter D, Mdege N, Stirk L, Sowden AJ, Godfrey C. Interventions for alcohol and drug problems in outpatient settings: A systematic review. Drug Alcohol Rev 2013;32:356–367]